2005
DOI: 10.1021/jp044947p
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Mobility of Tethered Vesicle−DNA Assemblies

Abstract: Supported lipid membranes are particularly attractive for use in biochemical assays because of their resistance to nonspecific adsorption and their unique ability to host transmembrane proteins. Although ideal for use in many surface-based detection techniques, supported bilayers can make the incorporation of proteins problematic due to the steric constraints of the underlying substrate. A recently developed strategy overcomes this obstacle by tethering liposomes to supported lipid bilayers via cholesterol-tag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 28 publications
4
114
0
Order By: Relevance
“…Liposomes had been assembled on solid interfaces, where the anchoring points remain fixed and hence the liposomes are laterally immobile [109][110][111], as well as fluid interfaces such as surface supported lipid bilayers, where the liposomes are then free to diffuse in two dimensions [112][113][114][115][116].…”
Section: Reduced Dimensions: Assembly On Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes had been assembled on solid interfaces, where the anchoring points remain fixed and hence the liposomes are laterally immobile [109][110][111], as well as fluid interfaces such as surface supported lipid bilayers, where the liposomes are then free to diffuse in two dimensions [112][113][114][115][116].…”
Section: Reduced Dimensions: Assembly On Surfacesmentioning
confidence: 99%
“…The lateral mobility of planar bilayer-tethered liposomes has been characterised by FRAP [112] and single particle tracking [115]. FRAP studies with cholesterol-tagged DNAs found that liposome mobility was independent of tether length (in the range 15 30 bases) and liposome diameter (in the range 30 100 nm) [112].…”
Section: Reduced Dimensions: Assembly On Surfacesmentioning
confidence: 99%
“…18,19 However, to the best of our knowledge, this is the first study of vesicle-vesicle interactions mediated by the hybridization between complementary DNA strands. We use ssDNA oligonucleotides with a cholesterol modification on one of the ends (chol-DNA).…”
Section: Introductionmentioning
confidence: 99%
“…5͒. This and similar DNA constructs have been and are currently used by us and others for site-selective sorting of vesicles in combination with optical wave guide lightmode spectroscopy ͑OWLS͒, 41 for studies of the lateral mobility of tethered vesicles 42,43 including the kinetics of DNA-hybridization induced docking events 44 and for studies of three-dimensional networks of lipid vesicles, 45 in which case the full sensing volume of conventional SPR sensors can be efficiently utilized. 46 As demonstrated in Sec.…”
Section: B Site-selective Sorting Of Tlvsmentioning
confidence: 99%